Developing Physics Comprehensive Contextual Teaching Material Based on KKNI in Work and Energy for High School Students - Fitria Arifiyanti; Suparno Suparno (Variabel, 2019)
This research aimed to (1)produce Physics Comprehensive ContextualTeaching Material (PhyCCTM)based on KKNI which feasible in work and energy,(2)know the improvement of student’s higher-order thinking skills (HOTS)by using PhyCCTM based on KKNI in work and energy, (3)know the improvement of student’s scientific attitude by using PhyCCTM based on KKNI in work and energy, (4) know the effectivity of PhyCCTM based on KKNI in work and energy to improve student’s HOTS and scientific attitude. The procedure of development in this research referred to the steps procedural model adapted from Borg & Gall model, which has six steps. Data collection techniques used interviews, written tests, questionnaires, and observations. Data analysis technique for the improvement in students HOTS and scientific attitude used the gain score to see its effectiveness and MANOVA to see the significance of the difference between the control class and the experimental class. The results of this research were as follows. (1) PhyCCTM based on KKNI can be reasonably used with the category of "Very Good." (2) PhyCCTM based on KKNI can improve student’s higher-order thinking skills. (3) PhyCCTM based on KKNI can improve a student’s scientific attitude. (4) PhyCCTM based on KKNI can improve student’s higher-order thinking skills and scientific attitude.